2016
DOI: 10.3390/polym8050186
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Unification on the Stress-Strain Model of Concrete Subjected to High Passive Confinement by Fiber-Reinforced Polymer

Abstract: Abstract:The stress-strain behavior of concrete can be improved by providing a lateral passive confining pressure, such as fiber-reinforced polymer (FRP) wrapping. Many axial stress-strain models have been proposed for FRP-confined concrete columns. However, few models can predict the stress-strain behavior of confined concrete columns with more than two specified cross-sections. A stress-strain model of FRP-confined concrete columns with cross-sectional unification was developed in this paper based on a datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…Figure 5 shows the axial compressive stress-strain behavior of all the FRP-confined FLWAC cylinders. Much like the stress-strain curves of FRP confined NC [ 29 , 52 , 53 , 54 ], the curves for FRP-confined FLWAC also display a monotonically ascending bi-linearity, and the stiffness rapidly decreases after the transition zone. Previous researchers have intensively studied the stress determined the transition zone for FRP-confined NC, and it is concluded that the stress is around the strength of the unconfined concrete [ 17 ].…”
Section: Test Resultsmentioning
confidence: 99%
“…Figure 5 shows the axial compressive stress-strain behavior of all the FRP-confined FLWAC cylinders. Much like the stress-strain curves of FRP confined NC [ 29 , 52 , 53 , 54 ], the curves for FRP-confined FLWAC also display a monotonically ascending bi-linearity, and the stiffness rapidly decreases after the transition zone. Previous researchers have intensively studied the stress determined the transition zone for FRP-confined NC, and it is concluded that the stress is around the strength of the unconfined concrete [ 17 ].…”
Section: Test Resultsmentioning
confidence: 99%
“…The compared results are shown in Figure 7e,f, in which the error index AV values were 0.24 and 0.22 for ultimate strain and stress, respectively, and IAE values were 0.24 and 0.22 for ultimate strain and stress, respectively. The error indexes AV and IAE [2,9,[31][32][33] are defined in Equations (3) and (4), respectively. It can be seen that there is an error between the theoretical value and the experimental value.…”
Section: The Ultimate Conditionmentioning
confidence: 99%
“…where f 30 is the concrete compressive strength of 30 MPa. (9) When the strain rate ̇ is equal to ε0 (10 -5 /s), Equation 9degenerates to the elastic limit stress of the confined concrete under quasi-static loading. Therefore, Equation (9) is reasonable.…”
Section: Elastic Limit Stress F Omentioning
confidence: 99%
See 2 more Smart Citations